Tax Burden of Agricultural Enterprises in Ukraine (Agricultural Engineering, 2021)
Agriculture is one of the leading sectors of the Ukrainian economy, and the state pays special attention to its development. One of directions of the state’s support for agriculture is implementation of tax preferences due to which agricultural enterprises have a lower tax burden. The optimal level of the tax burden is an important factor in ensuring the positive dynamics of business activity in agriculture, as well as socio-political stability. The objective of the article is to determine the impact of recent changes in the Ukrainian tax legislation on the tax burden of agricultural enterprises, as well as the possible impact of current draft laws. The article examines features of the tax legislation in Ukrainewith regard to agricultural producers and its changes in recent years - increasing a single tax rate, introduction of indexation of land regulatory, monetary valuation, abolition of the special regime of a value added tax. The advantages and disadvantages of using a simplified taxation system by agricultural enterprises are considered. the study’s outcome comprises recommendations for agricultural enterprises to choose a tax system with the lowest tax burden, as well as recommendations for improving the tax legislation of Ukraine using preferential VAT rates for agricultural enterprises and a tax on withdrawn capital.